Elementary school children’s pragmatic skills: What children learn between five and ten - Feider, Helga; Saint-Pierre, Madeline (Lenguas Modernas, 2017)
This article presents data on linguistic and paralinguistic forms used by three groups of children aged 5:6, 8:6, 10:6 years in a situation of dyadic role play. The dara were analysed in terms of speech act types and concordances were established documenting the surface forms associated with each speech act type (illocutionary force). The results show a diversification of linguistic forms and an increasing use of more complex forms with age. Paralinguistic forms of expression tend to decrease with age, while older children tend to be more selective in the use of these forms. The results are interpreted with reference to both pragmatic, linguistic and socio-cognitive theories of language development.